Analysis of knowledge generation in the El Cielo Biosphere Reserve, Mexico, and the link to its management program - Caballero-Rico, Frida Carmina (Universidad Autónoma de Tamaulipas, 2020)
The generation, systematization and knowledge transfer about biodiversity is a fundamental input for its conservation and the inclusion of the community. El Cielo Biosphere Reserve (ECBR) in Tamaulipas, Mexico, is a natural area protected due to the characteristics of its biotic and abiotic resources. The objective of this research was to characterize the current state of the generated knowledge about El Cielo Biosphere Reserve and its relationship with its management program. A qualitative and quantitative search, classification, and review of the primary sources in the Web of Science, Scopus, and Redalyc databases was performed. This information was contrasted with the content of the ECBR Management Program. Results show an indirect association between publications and the management program with the absence of publications in the culture, communication, and management subprograms. The need to systematize the addressed topics was also evident. The main achievement of this work is the integration, mapping, and systematization of publications, which establishes a baseline for future studies. The existing knowledge about ECBR, published in scientific journals, was conducted from a disciplinary approach in the field of Biology. There is evidence that it was used to prepare its most recent management program and that it impacts at least 20 % of the actions included in the document. However, the process for the transfer of knowledge was indirect, and new transdisciplinary approaches are required to address the existing socio-ecological problems.